FRAUD PREVENTION THROUGH INTERNAL CONTROL AND MORAL SENSITIVITY (Case Study on a State Owned Bank) - Rudi Ginting; Herman Sjahruddin; Amtai Alaslan; Deni Riani; Endah Prawesti Ningrum (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research is motivated by increasing acts of fraud. This study aims to determine and analyze the effect of internal control and moral sensitivity on fraud prevention. This research is a quantitative research with a case study approach. This case study was conducted at State-Owned Enterprise Banks (BUMN) including Bank Mandiri, Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), and State Savings Bank (BTN). The sample in this study was 100 employees with the sampling technique the sample is random sampling. Data collection uses a questionnaire distributed via google form. The instruments used have been tested for validity and reliability. The collected data were analyzed using the classical assumption test and multiple linear regression using excel and SPSS. The results of this study indicate that 1) Internal Control has a positive and significant effect on Fraud Prevention, 2) Moral Sensitivity has a positive and significant effect on Fraud Prevention, and 3) Internal Control and Moral Sensitivity have a positive and significant effect on Fraud Prevention. The results of this study indicate that if a company wants to improve fraud prevention, the company must improve internal control and moral sensitivity.